IUBIREA SFINTEI TREIMI – IZVORUL, TEMEIUL VALORILOR UMANE ȘI LIBERTĂȚII RELIGIOASE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Love of the Holy Trinity – The Source, the Basis of Human Values and Religious Freedom.The service of Jesus Christ is continuous and free because „My Father works until now; and I also work” ( John 5,17) for „God did not send His Son into the world to judge the world, but that the world should be saved through Him” ( John 3,17). So, being „servants of Jesus Christ” (Romani 15,16), like Paul the Apostle, we must „point out these things to the brothers, as good servants of Christ Jesus, nourished by the words of faith and sound instruction” (I Timothy 4,6). That is why the freedom of Christ the Risen Saviour is truly the model of our freedom and the source of power that graciously helps and strengthens our freedom. That is why the Saviour Jesus exhorts: „remain in me and I also remain in you, apart from me you can do nothing” ( John 15,4–5). Thus, our Lord Jesus Christ show sus that our life is anchored into existence and in order to gain true freedom so that you can fulfil the commandment of love towards God and towards your neighbour (Matthew 22,37–39). The goal of the man is his eternal existence in God; this goal was presented by God when he created the man free from any external constraint. Man`s free work is all the more perfect as it is the same as God`s.